2021
DOI: 10.1111/emre.12490
|View full text |Cite
|
Sign up to set email alerts
|

Have your cake and eat it? Combining structure and agency in management research

Abstract: This paper presents an explanatory logic and an empirical illustration of how Stones’ strong structuration theory, specifically the methodological brackets of agent's conduct and agent's context analysis can be applied within case study research. The value of strong structuration theory, and the methodological bracketing tool, is its proximity to empirical research and the provision of robust guidelines which enable researchers to resolve the methodological challenges of combining structure and agency within r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Employees influence the control by monitoring themselves (i.e., self‐control) and their colleagues (i.e., peer control) and taking actions that influence the efficacy of organizational and managerial control (e.g., by refusing to fill out reports). In so doing, they are affected by their perception of the context in which they are embedded (Kennedy et al, 2021). Organizational control is thus not only a coercive function to enhance efficiency but also a consequence of human sense‐making and meaning‐giving processes (Sitkin et al, 2010).…”
Section: Organizational Control: An Extended Perspectivementioning
confidence: 99%
“…Employees influence the control by monitoring themselves (i.e., self‐control) and their colleagues (i.e., peer control) and taking actions that influence the efficacy of organizational and managerial control (e.g., by refusing to fill out reports). In so doing, they are affected by their perception of the context in which they are embedded (Kennedy et al, 2021). Organizational control is thus not only a coercive function to enhance efficiency but also a consequence of human sense‐making and meaning‐giving processes (Sitkin et al, 2010).…”
Section: Organizational Control: An Extended Perspectivementioning
confidence: 99%
“…Stones (2015, p. 27) identifies a range of facets of the environment (such as institutional and individual actors, networks, forces, and pressures), extending it to include relations and conditions surrounding the agent. Although some aspects of the external field might appear to be “objective” in some sense, the external environment of the actor is always viewed through the actor's internal world and their experiences and words, so extensive engagement with actors is required to operationalize strong structuration adequately (Kennedy et al, 2021; Stones, 2005).…”
Section: Theoretical Underpinnings and Research Questionsmentioning
confidence: 99%
“…Strong structuration builds on the fundamentals of Giddens's original work, but importantly, brings the theory closer to empirical research. It achieves this through the deployment of methodological bracketing (Kennedy et al, 2021), an approach that encourages a focus on the analysis of an agent's context, while holding the analysis of an agent's conduct in abeyance as far as possible, and then reversing the approach to focus on conduct. This bracketing approach and the insight to be gained by exploring both context and conduct are central to the strength of the theory for empirical work.…”
Section: Theoretical Underpinnings and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Omer, M. S. et al analyzed the relationship between organizational structure and construction risk management, and the results showed that specialization, centralization, and risk management of the industry had a positive relationship [11]. Kennedy, A. et al studied the main components of corporate management structure and analyzed the relationship between management structure and corporate risk [12]. Ibrahim, A. H. et al studied the level of enterprise risk management as well as corporate governance and analyzed the effect of corporate governance on firm performance improvement [13].…”
Section: Literature Reviewmentioning
confidence: 99%